Análise morfológica e topográfica das células ganglionares da retina do caititu (Tayassu tajacu) - COSTA, Kelly Helorany Alves (2014)
In the Amazon there are several different wild animals species, becoming this way a good environment to investigated about compared physiology. Among this species, the caititu, Tayassu tajacu, stood out. This animals is located in central America and Latin America. There are many publications around morphology of sexual organs, meat and blood of the catitu. Although, regarding studies about visual’s morphology are scarce. Facing this reality, the present study investigated a morphology and topography of ganglion cells of Tayassu tajacu’s retina. Were used six retina, from eight animals, Both sexes of the species Tayassu tajacu. The caititu born and raised in captivity in the Brazilian company of research known as Embrapa/Pará. Were slaughtered according to the rules of animals ‘s management to subsequent removal and attachment of eyes. The retinas were dissected and stained using Nissl technique to ganglion cells of view, displaced amacrine, red blood cells, microglia cells and components of vascularization. A count of ganglion cells was made a long the horizontal and vertical axis. Being the number of ganglion cells by field converted into density values. The different regions of the retina were analyzed as the cellular density, obtaining the medium value of the density 351,822 ± 31,434 CG/mm². Verified different of the density between the studies regions : The dorsal region had a medium density and standard deviation 894 ± 44 CG/mm², the ventral region 894 ± 1 CG/mm²; the nasal region 1.403 ± 43; the temporal region with 1596 ± 251. The average peak density located approximately 3.13 mm from the dorsal direction and 6.77 mm in the temporal direction of the optic nerve, was 6767 GC / mm². Check there are two specialized regions, the visual streak region and the area temporalis. The visual streak located in the horizontal direction of the nasal region to temporal, presenting higher cellular density, possibly providing better panoramic vision from the environment and detecting the objects in the horizontal direction. Already the temporalis area, located within the visual range, provides increased visual acuity and spatial resolution, the environment that they live. These results allow to start comparisons between morphophysiological the retina of peccaries with other animal species.